Design and characterization of bivalent compounds as potential neuroprotectants for Alzheimer's disease: Impact of the spacer on biological activity. Issue 6 (1st April 2018) - He, Liu; Boice, Ashley; Liu, Kai; Yan, Xing; Jiang, Yuqi; Zhang, Shijun
Graphical abstract: Abstract: In our continuing efforts to develop bivalent compounds as potential neuroprotectants for Alzheimer's disease, a series of bivalent compounds that contain cholesterylamine and an extended spacer were synthesized and biologically characterized. Our results demonstrated that incorporation of a piperazine ring into the spacer composition significantly improved the protective potency in MC65 cell models. Our results also suggested that the optimal spacer length for such bivalent compounds ranges from 17 to 21 atoms, and further spacer extension beyond 21 atoms results no further optimization. Notably, incorporation of a piperazine ring into the spacer diminished the biometal chelating capacity for these bivalent compounds, thus suggesting structural flexibility of these compounds in interactions with metals. Collectively, the results provided valuable guidance to develop new bivalent compounds as neuroprotectants for Alzheimer's disease.